Analysis of Factors That Influence The Preference of Cognitive Style Learning Model when Using Technology Devices - Nfn Bahrawi (BBPSDMP KOMINFO MAKASSAR, 2020)
People's cognitive learning styles are different, identify learning styles early on considered able to increase effectiveness in the learning process, even in some studies submitted can improve achievement. In the process of learning, everyone has a variety of ways, some learn by listening, some learn by reading and learning by finding. This study wants to predict how much influence the factors (frequency of internet usage, number of instant messaging (IM) groups followed, and gender of one's learning style preferences when utilizing technology such as computers / laptops or smartphones. The analysis method used in this research is Multinomial Logistic Regression. The results showed, the more IM groups followed, the more likely a person was to use a